2009
DOI: 10.1007/s11099-009-0055-y
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of 5-aminolevulinic acid treatment on leaf photosynthesis is related with increase of antioxidant enzyme activity in watermelon seedlings grown under shade condition

Abstract: Watermelon [Citrullus lanatus (Thunb.) Mansfeld] is a photophilic plant, whose net photosynthetic rate was significantly decreased when seedlings were grown under low light condition. However, treatment with 100 mg kg -1 5-aminolevulinic acid (ALA) could significantly restore the photosynthetic ability under the environmental stress. The parameters of leaf gas exchange, chlorophyll modulated fluorescence and fast induction fluorescence of the ALA-treated plants were higher than that of the control. Additionall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 31 publications
4
31
0
Order By: Relevance
“…ALA might improve the photochemical efficiency of PSII reaction center. Whether the darkadapted or light-adapted maximal photochemical efficiency, it has been reported that ALA had significant effect (Sun et al, 2009a;Wang et al, 2010). Recently, the similar effect was confirmed in the transgenic tobacco (Zhang et al, 2010).…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…ALA might improve the photochemical efficiency of PSII reaction center. Whether the darkadapted or light-adapted maximal photochemical efficiency, it has been reported that ALA had significant effect (Sun et al, 2009a;Wang et al, 2010). Recently, the similar effect was confirmed in the transgenic tobacco (Zhang et al, 2010).…”
Section: Discussionmentioning
confidence: 80%
“…Previous reports have demonstrated that ALA treatment can improve the net photosynthetic rate in spinach (Nishihara et al, 2003), melon (Wang et al, 2004), pakchoi (Wang et al, 2004b), radish (Hotta et al, 1997b;Wang et al, 2005b), strawberry (Liu et al, 2006) and watermelon (Sun et al, 2009a), under normal or stress conditions. The result of this work confirmed that exogenous ALA at a concentration of 0.5 mg/L could increase the net photosynthetic rate of pear leaves ( Fig.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations